KELUARGA BERENCANA (Studi Analisis Fatwa Ali Jum’ah Dalam Kitab Al-Fatâwâ Al-Islâmiyyah) - Sri Aisyah; Zainal Azwar (Jurnal AL-AHKAM, 2020)
The  problem  in  this  study  is  the  existence  of  Ali  Jum'ah's  opinion  about  the permissibility of doing family planning in terms of (tahdîd al-Nasl) birth restriction. The objectives to  be  achieved  in this  study  are  to  determine  the  factors  causing  Ali  Jum'ah's  disagreements  with most  muftis  in  Egypt  regarding  family  planning,  knowing  the  arguments  used  by  Ali  Jum'ah regarding family planning, and analyzing the influence of certain schools of thought on Ali Jum ' ah about  family  planning.  The  results  of  the  study  can  be  concluded  as  follows:  first,  the  factors causing  the  difference  in  opinion  between  Ali  Jum'ah  and  most  muftis  in  Egypt  regarding  family planning  due  to  differences  of  opinion  in  terms  of  tandzîm  al-Nasl  and  tahdîd  al-nasl,  the  time period  for  performing  'azl  and  the  influence  of  the  school  of  thought  on  abortion.  Second,  the argument used by Ali Jum'ah regarding family planning is the ability of 'azl in Islam as narrated by Bukhari  and  Muslim.  While  the  ability  to  terminate  the  womb,  Ali  Jum'ah  did  not  mention  the arguments related to this in his fatwa. Third, Ali Jum'ah allowed 'azl not to be influenced by certain schools  of  thought,  because  in  general  the  Imams  of  madzhab  allowed'  azl  with  the  wife's permission. Meanwhile, Ali Jum'ah's skills regarding abortion were influenced by the Hanafi school of thought.Keywords: Family Planning, Fatwa, Ali Jum'ah, Kitab Al-Fatâwâ Al-Islâmiyyah